Tata Kelola Sampah Dalam Pembuatan Ecobrik Solusi Ramah Lingkungan Di Sekolah MIS Maura El-Mumtaz Kota Binjai - Aulia, Tasya; Lubis, Annisa Putri; Dea Indriani; Saragi, Ayu Pitaloka; Miftahul Jannah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The dangers of plastic waste are common and disturb both the water, land and air. Ecobricks are a creative way to reduce plastic waste by putting clean plastic waste into plastic bottles and the results will be used for human benefit. Making ecobricks is not yet popular among the wider community. This service activity will provide benefits to various parties, including the community, community service participants and the government. The targets for this service activity are Maura El-Mumtaz Elementary School students in the Tanah Seribu sub-district, Binjai City. Based on the results of community service activities that have been carried out, it can be seen that students can make seats from ecobricks. It is hoped that students will be able to express many more ideas for making ecobricks, not only making them in the form of chairs but also in other shapes. So this can be used as a business opportunity for the community